2017
DOI: 10.1038/s41598-017-18262-5
|View full text |Cite|
|
Sign up to set email alerts
|

Human Sexual Cycles are Driven by Culture and Match Collective Moods

Abstract: Human reproduction does not happen uniformly throughout the year and what drives human sexual cycles is a long-standing question. The literature is mixed with respect to whether biological or cultural factors best explain these cycles. The biological hypothesis proposes that human reproductive cycles are an adaptation to the seasonal (hemisphere-dependent) cycles, while the cultural hypothesis proposes that conception dates vary mostly due to cultural factors, such as holidays. However, for many countries, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…In this paper we examine the first mechanism: the relationship between ambient temperatures and sexual activity. Although previous papers have studied the seasonal variation in sexual activity (Fortenberry et al 1997;Levin, Xu, and Bartkowski 2002;Markey and Markey 2013;Rodgers, Harris, and Vickers 1992;Udry and Morris 1967;Wood et al 2017), our paper is among the first to analyze the effect of ambient temperatures explicitly. To our knowledge, only Wilde, Apouey, and Jung (2017) have analyzed temperature-induced changes in sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we examine the first mechanism: the relationship between ambient temperatures and sexual activity. Although previous papers have studied the seasonal variation in sexual activity (Fortenberry et al 1997;Levin, Xu, and Bartkowski 2002;Markey and Markey 2013;Rodgers, Harris, and Vickers 1992;Udry and Morris 1967;Wood et al 2017), our paper is among the first to analyze the effect of ambient temperatures explicitly. To our knowledge, only Wilde, Apouey, and Jung (2017) have analyzed temperature-induced changes in sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Note that this approach assumes that affect can be measured from its expression through human communication. While a substantial level of noise can be expected when using these text analysis methods to quantify emotions, the use of large-scale data from social media and other digital resources allows the analysis of individual and collective emotions through temporal and structural patterns [16,19,21,33,34]. We quantify valence and arousal expressed in each status update through unsupervised methods that compute mean scores over stemmed terms in a text [35].…”
Section: Text Analysis Of Affective Expressionmentioning
confidence: 99%
“…These results are very similar when using the alternative sentiment analysis method, as reported The memory patterns of our model, while consistent with previous research, could also be explained by collective and cultural synchronization processes that influence emotional expression. For example, seasonal greetings such as "happy New Year" or "merry Christmas" could introduce artifacts in our measurement as manifestations of collective mood [34]. We account for these effects in our analyses, we repeated the model fits including additional inter-individual weekly baselines for valence and arousal.…”
Section: Affect Dynamics Model Fitsmentioning
confidence: 99%
“…Although the accuracy of Google trends data alone has been problematic for epidemic flu modeling (21), such data add value in combination with other health data (22). Several studies have also shown that social media analysis is useful for: tracking and predicting disease outbreaks such as influenza (11,23), cholera (24), Zika (25), and HIV (26); playing an important role in pharmacovigilance (3,(27)(28)(29)(30)(31); and measuring public sentiment and other signals associated public health issues such as depression (4,(32)(33)(34), human reproduction (35), vaccination rates (36,37), and mental disorder stigma (13).…”
Section: Introductionmentioning
confidence: 99%